Knowledge Management Maturity Level Assessment ((Case Study Of PT. XYZ) - Ramadhani, Sigit; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2012)
Knowledge Management nowadays is largely implemented in every organization and often mentioned in publications, but little shows about the relation with the organization performance itself. KM in XYZ has been started in 2008, at least since a global team under HR organization was established. Some KM initiatives were born by the team. But some sample conditions shows otherwise. This study helps to explain the use of KM assessment and the important factors to be improved in relation with the organization performance. This study utilizes APO’s approach in assessing the organization KM maturity level through qualitative survey. Analysis of this research shows the different maturity level for each type of gender, age, and position in the organization and taken further to see the relation with the organization performance from its financial reports. Keywords: APO, knowledge management, level, maturity.